2006
DOI: 10.1203/01.pdr.0000227479.73003.b5
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Reveals Novel Genes Induced by Mechanical Forces in Fetal Lung Type II Epithelial Cells

Abstract: Mechanical forces are essential for normal fetal lung development. However, the cellular and molecular mechanisms regulating this process are still poorly defined. In this study, we used oligonucleotide microarrays to investigate gene expression in cultured embryonic d 19 rat fetal lung type II epithelial cells exposed to a level of mechanical strain similar to the developing lung. Significance Analysis of Microarrays (SAM) identified 92 genes differentially expressed by strain. Interestingly, several members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Detailed comparisons with another gene microarray study, which revealed a highly altered expression of 18 genes in primary rat AT I-like cells [24], did not identify any similar changes. However, comparisons with the gene microarray study of Wang et al ., which revealed 57 differentially expressed genes in primary fetal AT II cells [11], confirmed similar changes for at least four up-regulated genes (SLC7A3, SLC6A9 and SLC29A3 coding for solute carrier (SLC) group of membrane transport proteins, and TRIB3 (Tribbles homolog 3)) in A549 cells (data not shown).…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Detailed comparisons with another gene microarray study, which revealed a highly altered expression of 18 genes in primary rat AT I-like cells [24], did not identify any similar changes. However, comparisons with the gene microarray study of Wang et al ., which revealed 57 differentially expressed genes in primary fetal AT II cells [11], confirmed similar changes for at least four up-regulated genes (SLC7A3, SLC6A9 and SLC29A3 coding for solute carrier (SLC) group of membrane transport proteins, and TRIB3 (Tribbles homolog 3)) in A549 cells (data not shown).…”
Section: Resultsmentioning
confidence: 54%
“…In contrast to expression studies investigating individual strain-regulated genes in lung epithelial cells, our and other gene microarray studies investigating a large panel of genes were not performed in a time-dependent manner [11,22,23]. Merely one study analyzed the entire gene expression profile at two time points, but the maximum time was already at 6 hours of cyclic distension [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations